2006
DOI: 10.1038/sj.bjp.0706677
|View full text |Cite
|
Sign up to set email alerts
|

Species‐dependent smooth muscle contraction to Neuromedin U and determination of the receptor subtypes mediating contraction using NMU1 receptor knockout mice

Abstract: 1 The peptide ligand neuromedin U (NMU) has been implicated in an array of biological activities, including contraction of uterine, intestinal and urinary bladder smooth muscle. However, many of these responses appear to be species-specific. This study was undertaken to fully elucidate the range of smooth muscle-stimulating effects of NMU in rats, mice and guinea-pigs, and to examine the extent of the species differences. In addition, the NMU1 receptor knockout mouse was used to determine which receptor subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
7
19
0
Order By: Relevance
“…This lack of functional desensitization was apparent irrespective of the interval between applications and at least with a 30-min interval allowed noncumulative concentration-response curves to be constructed with individual tissue strips. The potency of NmU (pEC 50 values, 7.5-7.8) is consistent with its potency in other gastrointestinal smooth muscle preparations of the rat (pEC 50 values, 6.4 -8.4;Prendergast et al, 2006). A clear paradox in the present study is the ability of NmU to mediate repetitive contractions of colonic smooth muscle strips but an inability to mediate repetitive Ca 2ϩ transients in cultured colonic smooth muscle cells.…”
Section: Neuromedin U Signaling In Smooth Musclesupporting
confidence: 85%
See 2 more Smart Citations
“…This lack of functional desensitization was apparent irrespective of the interval between applications and at least with a 30-min interval allowed noncumulative concentration-response curves to be constructed with individual tissue strips. The potency of NmU (pEC 50 values, 7.5-7.8) is consistent with its potency in other gastrointestinal smooth muscle preparations of the rat (pEC 50 values, 6.4 -8.4;Prendergast et al, 2006). A clear paradox in the present study is the ability of NmU to mediate repetitive contractions of colonic smooth muscle strips but an inability to mediate repetitive Ca 2ϩ transients in cultured colonic smooth muscle cells.…”
Section: Neuromedin U Signaling In Smooth Musclesupporting
confidence: 85%
“…Of relevance to the present study are the observations that NmU mediates contraction of canine (Westfall et al, 2001) and human colon (Jones et al, 2006) but not colon from rat, guinea pig, or mouse (Benito-Orfila et al, 1991;Prendergast et al, 2006). The lack of a direct effect of NmU on contraction of mouse colon has been supported by a recent study, although it did potently enhance electrically stimulated, nerve-evoked contractions, possibly through prejunctional effects within the enteric ganglia (Dass et al, 2007).…”
Section: Neuromedin U Signaling In Smooth Musclesupporting
confidence: 68%
See 1 more Smart Citation
“…Our observation that NMU is expressed by neurons from thoracic DRG suggests that the coordinated action of neurons and chemosensory cells could promote tissue-based, ILC-dependent type 2 immune responses. Given the importance of smooth muscle contraction in the clinical manifestations of allergic diseases, it is intriguing that NMU can induce both smooth muscle contraction 44 and ILC2-driven inflammation. Neuronal activation following inhalation of noxious substances or allergens could potentially trigger both processes, simultaneously promoting physical expulsion and allergic immunity to the provoking stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…A direct, dose-dependent contractile effect of NmU has been detected for different organs and tissues of the gastrointestinal and genitourinary tracts, and an indirect, enhancing effect of electrically induced contraction has also been identified, suggesting that NmU can act as a direct contraction inducer or as a potentiator of another contraction stimulus (49 -54 ). Studies with mice deficient in NmU receptors have shown that gastrointestinal smooth muscle contraction is likely mediated by NMUR1, because contraction is unaffected in Nmur2 Ϫ/Ϫ mice but compromised in Nmur1 Ϫ/Ϫ mice (53,54 ). On the contrary, genitourinary tract contraction appears to involve both receptors, although compensatory effects in the absence of one receptor cannot be ruled out.…”
Section: Smooth Muscle Contractionmentioning
confidence: 99%